Occlusion-robust, low-latency optical tracking using a modular scalable system architecture - Köpfle, Andreas; Männer, Reinhard; Pott, Peter Paul; Schwarz, Markus; Scharf, Hanns-Peter; Wagner, Achim; Badreddin, Essameddin (Perspective in image-guided surgery, 2004)
This paper describes the development of an advanced optical tracking system for use in image guided surgery (IGS). Current tracking systems have a number of limitations: they are sensitive to occlusion of the line of sight, thus blocking space next to the operating table, their latency is too high for demanding applications like robotics control or tremor compensation, their accuracy drifts during operating time and aging. We present a new approach to tracking systems, addressing these problems. The system works with an arbitrary number of "intelligent" camera modules reducing occlusion problems and allowing adaption to tracking tasks of different complexity. The camera modules each feature an integrated hardware for image processing enabling high update rates and low latency times. A dynamic online recalibration of the system will be performed to assure constant precision over time.